Glaciotectonic disintegration of roches moutonnées during glacial ripping in east Sweden. Issue 1 (2nd January 2022) - Krabbendam, M.; Hall, A. M.; Palamakumbura, R. M.; Finlayson, A.
ABSTRACT: Roches moutonnées are typical landforms of glacial erosion developed in hard rocks, with an asymmetric profile caused by abrasion and lee-side plucking. In eastern Sweden, some roches moutonnées show extensive damage, including open fractures, disintegration into blocks, fracture caves and short boulder trains. Disintegration increases along ice-flow directions during deglaciation of the last Weichselian Fennoscandian Ice Sheet, indicating a subglacial origin: limited edge rounding can be explained by a combination of hard rock, slow abrasion rates and disintegration just prior to deglaciation. The roches moutonnées initially developed in kernels of gneissic rocks with a wide fracture spacing (large block size) and interlocking fracture pattern, and hence high overall rock mass strength. Dilated fractures and 'fracture caves' occur up to 15 m below the ice-bed interface. It is proposed that hydraulic jacking by overpressured water opened up the rock mass along pre-existing fractures. Jacking reduced rock mass strength, allowing glaciotectonic deformation of the roches moutonnées. Uneven hydraulic jacking led to uplift of individual fracture-bound blocks above the pre-existing smooth, abraded surface of the roches moutonnées, creating blunt, step-like edges. These edges allowed high ice pushing forces to act on large blocks: where blocks extend into the deeper rock mass, they further aided the disintegration of the rock mass. The disintegrated roches moutonnées can be regarded as transient features between intact bedrock and complete disintegration into boulders. The jacking-disintegration-transport sequence is characteristic of glacial ripping and very different from classic lee-side plucking.